The Impacts of British Accents on Students’ Dialects in a Speaking Class - Pratama Irwin Talenta; Rahmat Ari Wibowo (English Language and Education Spectrum, 2022)
The British people introduced their language to the Americans when they reached and occupied the lands of the indigenous people by sea between the 16th and 17th centuries. The British ways of communication and mass media played a very significant role in affecting dialect differences and modifying pronunciation and vocabulary into English standards, known as the received pronunciation (RP). This study is aimed to identify: (1) the students’ perception towards British accents in speaking class and (2) the particular impacts of the accents on students’ dialects when used in a classroom. This research applied a mixed-method, the sequential explanatory with the advanced quantitative (explanatory) and then a qualitative. In other words, the results of this research are made ​​in the form of quantitative data and supported by qualitative data in the form of narrative depth. The participants were non-English students who had a less understanding of British accents. To collect data, observations on some of the participants’ documents (archives, photographs, and field notes) and questionnaire, followed by in-depth interviews with the students. Furthermore, to get the validity of its findings, the triangulation validity of the data is discussed with researchers and colleagues who understand the areas studied. British Accents are expected to become a motivation and the standard of its assessment-based speaking skill level.